Morphofunctional features of isthmocele complicated by abnormal uterine bleeding - Z.I. Hladchuk; N.M. Rozhkovska; V.O. Sytnikova; S.M. Syvyi (Репродуктивная эндокринология)
Background. The frequency of cesarean section remains high, and in some countries it exceeds 40% of all deliveries. The prevalence of isthmoceles as a consequence of cesarean section according to different authors ranges from 19 to 84%. Symptomatic isthmoceles is most often accompanied by abnormal uterine bleeding in 30-55% of women. Objective of the study: to determine the functional, morphological and immunohistochemical features of isthmocele complicated by abnormal uterine bleeding. Materials and methods. A prospective study was conducted, 68 patients were under observation: 38 patients of reproductive age with isthmocele after cesarean section who sought medical care for abnormal uterine bleeding (group 1, the main) and 30 practically healthy women of the same age with a normal uterine scar (group 2, the control). Immunohistochemical examination was performed in paraffin sections. Primary and secondary antibodies were used to detect CD34, CD68 and CD138 markers. Results. Patients with isthmocele complicated by abnormal uterine bleeding have an increased body mass index, a higher frequency of dysmenorrhea, excessive menstruation, heavy menstrual bleeding, intermenstrual bleeding, anemia, compared with women with a complete uterine scar (p < 0.01). Isthmoceles in 84.2% of cases was associated with ultrasonographic and pathologic signs of adenomyosis, with insufficiently effective treatment of abnormal uterine bleeding noted in 78.9% of cases, and no effect of conservative treatment in 21.1% of cases. The high expression of CD34, CD68, CD138 markers in the areas of the isthmoceles complicated by abnormal uterine bleeding indicates the activity of adenomyosis and the presence of chronic endometritis, which determines the specificity of the clinical picture and requires improvement of treatment approaches. Conclusions. Accounting the functional, morphological and immunohistochemical features of isthmocoele complicated by abnormal uterine bleeding will improve the effectiveness of treatment of symptomatic isthmocoele.